Draft Annual Plan 1989-1990 Government of Mizoram - Planning Commission (Planning Commission, 1989)
Since Mizoram attained the status of U.T. in January 1972, the planning Commission approved an outlay of Rs. 275.00 lakhs for Mizoram for the Annual Plan of 1972-73. This outlay was enhanced to Rs. 437.00 lakhs in the later part of the year. Out of this provision only Rs. 355.23 lakhs was actually spent.
Government of Mizoram, Planning and Programme Implementation Department